Current Management Strategy for Osteoarthritis Patients: a Review - Dmitry E. Karateev; Lilia V. Luchikhina; Elena L. Luchikhina; George N. Golukhov (Вестник восстановительной медицины, 2022)
A strategic approach is crucial to the management of patients with osteoarthritis (OA). It should be based on the current understanding of the pathogenesis of OA as an inflammatory disease. A review of current clinical guidelines for the management of patients with OA shows significant differences in the evaluation of pharmacological approach, especially the place of symptomatic slow-acting drugs for osteoarthritis, (SYSADOA) and a certain consensus in relation to non-pharmacological methods (primarily exercise, patient education, body weight control, various physiotherapy methods, orthotics and massage/manual therapy). It should also be taken into account the international “treat to target” recommendations, the main idea of which is careful regular monitoring of the patient’s condition and adaptation of treatment tactics depending on the response to treatment. Based on the analysis of literature data and their own clinical experience, the authors developed an algorithm for the strategy of complex therapy of OA, including the following steps: 1) pain control (2-4 weeks), 2) inflammation control (4-6 weeks); 3) control over cartilage degradation (6 weeks – 12 months). For each stage, a specific combination of systemic pharmacotherapy (non-steroidal anti-inflammatory drugs, SYSADOA), intra-articular administration of glucocorticoids and hyaluronic acid, exercises and magnetotherapy (pulsed electromagnetic field) was proposed. A staged comprehensive strategy for the treatment of patients with OA should help to achieve control over the symptoms, while minimizing the duration of NSAIDs and avoiding polypharmacy, and further achievement of inhibition of structural progression.